The Effect of Using Digital Children’s Literature on Storynory.com to EFL College Students’ Vocabularies at English Department, FBS, UNP - Gumay, Qaula Harisya; Marlina, Leni (Universitas Negeri Padang, 2024)
Children's digital literature is a platform that can be used as an innovative learning media, especially for reading. The objective of this research is to examine whether incorporating digital literature for children from the website storynory.com can enhance the vocabulary of college students studying English as a Foreign Language (EFL). Quasi-experimental was used as a research design in this study with quantitative methods. The population of this research were students of Introduction to Literature classes, English Department, FBS, Universitas Negeri Padang (UNP). Then, using a cluster random sampling technique, the researchers selected two classes in the Introduction to Literature course for the 2022/2023 academic year at the English Department, FBS, UNP as an experimental class and a control class. The data in this research was gathered from the outcomes of both the pre-test and post-test tests of vocabulary. Researchers chose 100 vocabulary words from a selection of 15 stories available on the storynory.com website for testing. The results of this research show an increase in vocabulary in the post-test score of 0.23 after using the storynory.com website in the experimental class. This provides evidence that incorporating children's digital literature, particularly from storynory.com, positively influences the vocabulary of EFL students at UNP.